The creation of value in the supply chain of the Colombian health sector (2009)
Considered as a supply chain, the Colombian health sector is characterized here from the standpoint of its transaction costs and value adding processes. The analysis is basically referred to the design of the Colombian health system as established by local regulations, namely Law 100 of 1993 and Law 1122 of 2007. As to develop the characterization, the system is analyzed in its component functions: surveillance and control agents, health insurance companies, health service delivery (medical) institutions, users and the system's financial modes. The study shows how the complexity of the system has been designed to satisfy the needs of the Colombian population, but this interest in generating added value for the final user implies high transaction costs.